Effects of microwave-enhanced pretreatment on oil shale milling performance - Meng, Yang; Tang, Luyao; Yan, Yuxin; Oladejo, Jumoke; Jiang, Peng; Wu, Tao; Pang, Chengheng (Elsevier, 2019)
Oil shale, as an unconventional fossil fuel, exhibits unique properties compared with coal and other petroleum. Due to the nature of sedimentary rock, large amounts of inorganic mineral impurities in rock matrix reduce the grade of oil shale, whilst increase the grinding resistance. This investigation presents the effects of microwave-enhanced pretreatment on the nature of oil shale and compared with conventional preheating process. Two Chinese oil shale from Fushun and Xingsheng Deposits were grounded and sieved into a size fraction (1-1.18mm) and were cut into eighteen cube-shaped specimens respectively. The prepared samples were processed accordingly to investigate how the grindability changed, in comparison to that of raw samples, and how the fundamental chemical properties of oil shale were altered after pretreatment. Quantitive data were used to assess the effects of different pretreatment methods on oil shale milling performance in a lab-scale pulverizer along with the impacts on moisture content, chemical properties. The uniaxial compressive strength (σmax) of Fushun oil shale was reduced 63.1% and the breakage rate increased 44.9% by short exposure to microwave irradiation. In conclusion, microwave-enhanced pretreatment presents significant improvement in oil shale milling performance compared to conventional preheating process in terms of breakage rate (Si) and uniaxial compressive strength (σmax) which showed negligible alterations. © 2019 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/) Peer-review under responsibility of the scientific committee of ICAE2018 - The 10th International Conference on Applied Energy.